Tight quotients of Smale diffeomorphisms on surfaces - Mello, João Paulo Ferreira de (2023)
Given a diffeomorphism $f$ over a closed surface, two points are said to be zero-entropy equivalence if there exist a continuum containing both points and the continuum carries zero entropy. In this work we use this concept to prove that the quotient dynamics, by the zero-entropy relation, of a \\textit diffeomorphism, which is a subclass of Smale diffeomorphisms on surfaces, is a generalized pseudo-Anosov homeomorphism over a closed surface possibly having identified points.